COVID GEAS: COVID-19 National Survey in Patients With Systemic Autoimmune Diseases - Gracia, Borja Del Carmelo; Sáez, Luis; Pallarés, Lucio; Velilla, Jose; Marín, Adela; Martinez-Lostao, Luis; Simeón, Carmen Pilar; Fanlo, Patricia (Frontiers in Medicine, 2022)
Objectives: COVID-19 outcomes in population with systemic autoimmune diseases (SAD) remain poorly understood. The aim was to examine demographic and clinical factors associated with COVID-19 infection in people with rheumatic disease. Methods: Two phases cross-sectional survey of individuals with rheumatic disease in April 2020 and October 2020. COVID infection, severity of disease, age, sex, smoking status, underlying rheumatic disease diagnosis, comorbidities and rheumatic disease medications taken immediately prior to infection were analyzed. Results: A total of 1,529 individuals with autoimmunity disease diagnosis were included. Out of 50 positive patients, 21 required telephone medical assistance, 16 received assessment by primary care physician, 9 were evaluated in Emergency Department and 4 patient required hospitalization. Multivariate analysis was performed without obtaining differences in any of the systemic autoimmune diseases. Regarding the treatments, significant differences were found (p 0.011) in the treatment with anti-TNF-alpha agents with OR 3.422 (1.322-8.858) and a trend to significance (p 0.094) was observed in patients receiving mycophenolate treatment (OR 2.016 (0.996-4-081)). Conclusions: Anti-TNF-alpha treatment was associated with more than 3-fold risk of suffering from SARS-CoV-2 infection, although in all cases infection was mild. Cumulative incidence in patients with SAD was up to 5 times higher than general population but with great differences between autoimmune diseases.